Analyzing the impacts of informal institutional factors affecting gender inequality: Evidence from 43 countries. (December 2022) - Kim, Seh Young
Highlights: The effects of informal institutions, i.e., perceptions, on gender inequality were tested with disaggregate regression analyses. All seven factors in the main analyses and 53 out of 56 factors in the sub-analyses affected gender inequality at various significant levels. The results indicated that informal institutions affect people irrespective of gender or socio-economic level. The results underlined the necessity of government interventions to change gender-discriminatory attitudes and practices. Abstract: Gender inequality is a socio-culturally constructed concept that people often take for granted. Since informal institutions, built on culture and traditions, significantly contribute to gender bias, examining the institutional factors that play into this effect may help determine the underlying causes of gender inequality. This study adopted seven gender-related perceptions from the World Value Survey (WVS) Wave 7 to test the different effects of informal institutions in 43 countries, utilizing disaggregate regression analyses to reduce the heterogeneity of the data. Socio-economic factors, including gender, education level, and income level, were added in the sub-analyses to identify the additional impacts of informal institutions. All seven factors in the main analysis and 53 out of 56 factors in the sub-analyses affected gender inequality at various levels of significance. Interestingly, more women than men were supportive of gender-biased perceptions in the sub-analyses. The results demonstrate how informal institutions shape and influence people's thoughts and views around them regardless of gender or socio-economic level. Therefore, taking deliberate measures to change people's attitudes toward gender issues is critical. Based on the results, a series of policy recommendations is suggested: introducing citizen participation to enhance transparency and fight corruption, conducting gender inequality-related campaigns using various media platforms, increasing cooperation with international organizations and agencies to set up proper gender-related mechanisms, and ensuring equal access to resources and opportunities.